Osteoporotic Skull Lesions in Moose at Isle Royale National Park - Hindelang, Mary; Peterson, Rolf O. (Journal of Wildlife Diseases, 1996)
Osteoporotic lesions were evaluated in the skulls of moose (Alces alces) collected in Isle Royale National Park, Michigan (USA), from 1958 to 1994. Circular lesions which penetrated the outer table of the skull were distributed over the frontal and nasal bones asymmetrically in both sexes. About 32% of skulls recovered had some porotic lesions with slightly greater prevalence among males.